2020
DOI: 10.1002/eji.201948349
|View full text |Cite
|
Sign up to set email alerts
|

S1PR4‐dependent CCL2 production promotes macrophage recruitment in a murine psoriasis model

Abstract: The sphingolipid sphingosine‐1‐phosphate (S1P) fulfills distinct functions in immune cell biology via binding to five G protein‐coupled receptors. The immune cell‐specific sphingosine‐1‐phosphate receptor 4 (S1pr4) was connected to the generation of IL‐17‐producing T cells through regulation of cytokine production in innate immune cells. Therefore, we explored whether S1pr4 affected imiquimod‐induced murine psoriasis via regulation of IL‐17 production. We did not observe altered IL‐17 production, although psor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…CC chemokines majorly recruit T cells and monocytes, whereas CXC chemokines predominantly recruit neutrophils in psoriasis (34). For instance, enhanced CCL2 release by macrophages induces monocyte migration to the psoriasiform lesions in mice (35). CCL4L2 and CCL22 are pivotal chemokines in patients with psoriasis to stimulate the chemotactic infiltration of dendritic cells and macrophages (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…CC chemokines majorly recruit T cells and monocytes, whereas CXC chemokines predominantly recruit neutrophils in psoriasis (34). For instance, enhanced CCL2 release by macrophages induces monocyte migration to the psoriasiform lesions in mice (35). CCL4L2 and CCL22 are pivotal chemokines in patients with psoriasis to stimulate the chemotactic infiltration of dendritic cells and macrophages (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the widely acknowledged histopathological features of psoriasis include four major aspects: the inflammatory infiltration in dermis and epidermis, the abnormal biological behaviours (differentiation, hyperproliferation, and apoptosis) of keratinocytes, metabolic disturbance in skin tissue, and the tortuously increased dermal blood vessels and capillaries [37][38][39][40][41]. Firstly, among the 27 core targets, most of them (PTGS2, ILs, JAK2, STAT3, RELA, CCL2, CXCL8, EGF, IFNG, and TLR4) have been shown to be involved in abnormal inflammatory infiltration, which could regulate the differentiation and chemotaxis of lymphocytes, cytokines produced, and immunological inflammatory reaction in dermis and epidermis [42][43][44][45][46][47][48]. Secondly, RELA, MAPKs, JUN, and BCL2L1 are associated with the aberrant biological behaviours of keratinocytes in psoriasis [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 , namely, C-C Motif Chemokine Ligand 2, is a chemotactic factor which attracts monocytes and basophils but not for neutrophils or eosinophils and involves in immunoregulatory and inflammatory processes. A study of Schuster et al showed that S1pr4 activation increases CCL2 production which promotes macrophage infiltration in a murine psoriasis model [ 14 ]. TNF signaling pathway involves in a wide range of biological processes including cell survival, apoptosis, immunity, and inflammation.…”
Section: Discussionmentioning
confidence: 99%